2020
DOI: 10.2174/2212797613666200220141119
|View full text |Cite
|
Sign up to set email alerts
|

Study of Pulsation Pressures in the Stages of an Electric Submersible Pump at Shut-Off Under Various Speeds of Operation

Abstract: Background: Electric Submersible Pumps (ESPs) are widely used in agricultural fields, petroleum, and various other industries. These pumps are mostly driven at a constant speed since an A.C. motor is normally used as the drive. However, ESPs can also be operated at various speeds by employing a Variable Frequency Drive (VFD). Several patents have been published in ESP. Normally these pumps are started with the discharge valve at its closed position in order to control the starting current. When the ESP runs at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The motor and the pump assembly were submerged under water so the output power and speed of the motor could not be measured directly. Therefore, the actual speed (Nactual) of operation of the pump was estimated from the values of slip and input power values (Dhanasekaran & Kumaraswamy, 2017).…”
Section: Performance Tests At Various Speedsmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor and the pump assembly were submerged under water so the output power and speed of the motor could not be measured directly. Therefore, the actual speed (Nactual) of operation of the pump was estimated from the values of slip and input power values (Dhanasekaran & Kumaraswamy, 2017).…”
Section: Performance Tests At Various Speedsmentioning
confidence: 99%
“…A detailed study was carried out to find source of these peaks. The results have shown that these prominent peaks may be due to structural vibration of the casing of the pump (Dhanasekaran, 2017). The equations ( 4), ( 5) and ( 6) were used to calculate BPF and its harmonic components at various stages when the pump was operated at BEP under various speeds.…”
Section: Fast Fourier Transformationmentioning
confidence: 99%